Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$x_1,x_2$ are two positive values of x for which 2 cosx, $|cosx|$ and $(3sin^2x-2)$ are in geometric sequence. One possible value of $|x_1-x_2|$ can be equal to

a) $\frac{2\pi}{3}$ b) $\frac{\pi}{3}$ c) $2cos^{-1}(\frac{2}{3})$ d) $cos^{-1}(\frac{2}{3})$

Since 2 cosx, $|cosx|$ and $(3sin^2x-2)$ are in G.P therefore, $|cosx|^2 = 2cosx (3sin^2x-2) $ R.H.S. = $2cosx(3(1-cos^2x)-2)$ = $6cosx - 6cos^3x-4cosx$

$\Rightarrow cosx = 6-6cos^2x-4 = 2-6cos^2x$

$\Rightarrow 6cos^2x-cosx-2=0$

Therefore, cosx = $\frac{1 \pm \sqrt{1+24}}{12}$ $\Rightarrow cosx = \frac{1}{2}; \frac{-1}{3}$

Please guide further....

share|cite|improve this question
up vote 1 down vote accepted

I think you were on the right track, there was just a small mistake. I understand the problem as follows:

$$2\cos(x)=a,\quad |\cos(x)|=ar,\quad 3\sin^2(x)-2=ar^2$$

We get $$r=\frac{|\cos(x)|}{2\cos(x)}=\pm \frac{1}{2}$$ and consequently $$3\sin^2(x)-2 = 1-3\cos^2(x) = \frac{a}{4} = \frac{1}{2}\cos(x)$$

which gives

$$6\cos^2(x) + \cos(x) - 2 = 0$$

with the solutions

$$\cos(x) = \{\frac{1}{2}, -\frac{2}{3} \}$$

share|cite|improve this answer
But answer options are different could u please elaborate further... – sultan Apr 15 '13 at 11:54
So you still have to find $|x_1-x_2|$ when $\cos x_1=1/2$ and $\cos x_2=-2/3$, but presumably you know how to find the values of $x_1$ and $x_2$ that give you those cosines. – Gerry Myerson Apr 15 '13 at 11:56

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.